Immiserizing growth and endogenous protection - Clarete, Ramon L. (Journal of Development Economics)
This paper focuses on immiserizing growth in the two senses of Bhagwati (1958) and Johnson (1967), and how both the likelihood that either may occur and their extent can be affected by the presence of endogenous protection; i.e., quota and other forms of protection for which the ad valorem equivalent level of protection is endogeneously determined. We use a general equilibrium model of the Philippines due to Clarete (1984) to compute counterfactual equilibria involving changes in domestic policies, terms of trade, and resource endowments. Immiserizing growth, in the sense of Bhagwati, is less likely because the terms-of-trade fall required to offset the growth of resources has to be significantly larger if no distortions are in the model. Immiserizing growth in the sense of Johnson tends to be more likely if endogeneous protection is present. As unbalanced growth occurs focused on the factor intensive in the protected sector, resources are drawn out of the export sector and export earnings decline and, if the level of protection is endogenously determined, the welfare costs of protection increase.